(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
In Kosovo, except electrical energy, thermal power plants (TPP) annually produce more than 1.5 Mt of solid waste: Fly Ash (FA) and Bottom Ash (BA). Kosovo’s construction sector annually consumes around 1 Mt of cement. The environmental impact from cement production (consumption) is the emission of around 1 Mt of CO2. The focus of this study is the utilization of FA in concrete as cement replacement, which will indirectly mitigate the CO2 emissions from cement production. The properties of concrete with FA were investigated. For determining the optimum quantity of FA in concrete, four concrete mixes with different content of class C FA were tested. Density and consistence tests of FA fresh concrete, as well as tests of mechanical properties: compressive, tensile and splitting strength of FA hardened concrete specimens were performed. Concrete resistance to permeability was tested by measuring the depth of water penetration under hydrostatic pressure. The correlation between test results of concrete specimens with FA to reference concrete without FA was done. A 30% cement replacement by fly ash showed experimentally to be reasonable. The environmental benefit would be twofold: indirect decrease of 300,000 t of CO2 and removal of 125,000 m3 of industrial waste (FA).